Maestro of science : Omond McKillop Solandt and government science in war and hostile peace, 1939-1956 - Ridler, Jason Sean, 1975- (University of Toronto Press, 2015)
Jason S. Ridler draws on interviews and declassified records to paint a vivid picture of the influence and achievements of a Canadian leader in Cold War military research.